Radiographic study on premature eruption of permanent premolars due to premature loss of primary molar - Sukmasari, Susi; Awang Nor, Norazizah; Sabri, Mohamad Yazid (Lembaga Studi Kesehatan Indonesia (LSKI), 2012)
Introduction: Early detection of premature eruption of permanent premolar (PEPP) in case of premature loss of primary molar (PLPM) is need for treatment planning. Objective: To investigate relationship between PLPM and PEPP radiographicaly. Method: A retrospective study on total 196 OPGs of 6-9 year-old pediatric patients who attended at polyclinic Kulliyyah of Dentistry in Kuantan city, IIUM from 2009 to 2011. OPGs were scrutinized to find out their relationship and correlation. Results: Out of (196) 0PG, PLPM was observed in (105) OPGs and PEPP was found in 85 OPGs. Prevalence of PI among 196 children was (268) per 1000 children per year and that of PEPP was (1 per 1000 children per year. Among total (1568) studied teeth, (265) were PLPM and (5 PEPP. Ratio of PLPM to PEPP in OPGs was (10:8) while ratio of PLPM to PEPP in t of total teeth was (17:13). There was strong significant correlation (r= 0.91, p<0 between total number of PLPM teeth and those of PEPP. Conclusion: This study pr( that premature loss of primary molar leads premature eruption of permanent premol; also illustrated that premature loss of primary molars is one of pediatric dentistry is in Kuantan community.